ANALISIS TROJAN DAN SPYWARE MENGGUNAKAN METODE HYBRID ANALYSIS - Annisa Rizky Damanik (2023)
Malicious Software or malware is software created to damage a computer system. The increase in internet users is also in line with the increase in the use of software. However, there are still many users who still use pirated software because it is relatively free and easy to obtain. Pirated software is usually embedded with dangerous malware such as Trojans and spyware. Trojans are the most common type of malware found in computer systems with many cases. And spyware is a type of malware that is difficult to see its activity on a computer system, even anti-virus often cannot detect this type of malware. All crimes of spreading this malware are always related to stealing credit card information, internet banking and other cybercrimes. To prove that the software installed and used on a computer is malicious software, digital forensics is required by analyzing the software. Hybrid analysis technique is a combination of static and dynamic analysis which is suitable for analyzing malware activity. The author hopes that using this analysis method can prove traces of malicious Trojan and spyware activity in the software used.